2014
DOI: 10.1155/2014/473250
|View full text |Cite
|
Sign up to set email alerts
|

Side of Limb-Onset Predicts Laterality of Gray Matter Loss in Amyotrophic Lateral Sclerosis

Abstract: Conflicting findings have been reported regarding the lateralized brain abnormality in patients with amyotrophic lateral sclerosis (ALS). In this study, we aimed to investigate the probable lateralization of gray matter (GM) atrophy in ALS patients. We focused on the relationship between the asymmetry in decreased GM volume and the side of disease onset in patients with limb-onset. Structural imaging evaluation of normalized atrophy (SIENAX) and voxel-based morphometry (VBM) were used to assess differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 66 publications
(108 reference statements)
1
31
0
Order By: Relevance
“…DPR is correlated with the thickness of the right inferior temporal cortex, the postcentral cortex and the right paracentral cortex.Westenberg et al, 2014112/60GM volume reduction in the hippocampus and left subiculum.Larger ventricles are correlated to a lower ALSFRS-R score. Smaller basal ganglia, smaller limbic structures and larger ventricles are associated with shorter survival.Zhang et al, [28]43/43GM reduction in the left precentral cortex, left supplemental area and left postcentral gyrus. Reduction in neocortex volume, GM and WM volume and brain parenchymal fraction.GM volume reduction is most important in the motor cortex of the contralateral hemisphere of the limb of onset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPR is correlated with the thickness of the right inferior temporal cortex, the postcentral cortex and the right paracentral cortex.Westenberg et al, 2014112/60GM volume reduction in the hippocampus and left subiculum.Larger ventricles are correlated to a lower ALSFRS-R score. Smaller basal ganglia, smaller limbic structures and larger ventricles are associated with shorter survival.Zhang et al, [28]43/43GM reduction in the left precentral cortex, left supplemental area and left postcentral gyrus. Reduction in neocortex volume, GM and WM volume and brain parenchymal fraction.GM volume reduction is most important in the motor cortex of the contralateral hemisphere of the limb of onset.…”
Section: Resultsmentioning
confidence: 99%
“…However, some DTI studies used VBM to show that ALS vs. control differences in the fractional anisotropy (FA) of the precentral gyri were not due to atrophy [33, 34]. In other studies, cortical atrophy was not limited to the precentral gyri but extended to other regions of the frontal lobe [1824, 2628, 32, 35] - especially in apathetic patients with involvement of the cingulate cortex [27, 36]. Other regions involved include several parts of the temporal cortex [19–24, 32, 35], the hippocampus [24, 3739], the parietal cortex (mostly in the post-central cortex [18, 21, 23, 28]) and the insula [24].…”
Section: Resultsmentioning
confidence: 99%
“…both mono-and pluri-synaptic in primates, and essentially pluri-synaptic in adult mice [36], it is worth highlighting that many mouse models of the disease recapitulate CSN or SubCerPN degeneration [22,28,38,42,50,70,71]. In this regard, we recently showed that Sod1 G86R mice not only display pre-symptomatic CSN degeneration, but also that CSN and spinal motoneuron degeneration are somatotopically related [42], similarly to what had been described in ALS patients [46,53,72].…”
Section: Introductionmentioning
confidence: 75%
“…In clinics, ALS diagnosis relies on evidences for combined degeneration of CSN and MN. While the origin and propagation of the disease between the two neuronal populations has always been debated 34 , number of studies reported on the somatotopic relationship between cortical and spinal impairments [35][36][37] , ruling out the possibility that CSN and MN degenerations are independent, and rather supporting a propagation from one neuronal population to the other, whether descendent, from the cerebral cortex to the spinal cord, or ascendant, from the spinal cord to the cerebral cortex (not to be confused with the Wallerian or retrograde degeneration of the MN, from their axonal terminals to their cell bodies). In spite of its classical text book definition, ALS is highly heterogeneous and, amongst other parameters, relative upper (CSN) and lower (MN) motor neuron involvement and site of disease onset greatly vary across ALS patients 38 .…”
Section: Discussionmentioning
confidence: 99%